Seriously, less taxes? Tax reform's effects over labor supply (2015)
Using a matching and a difference in differences approach we analyzed the impact of a payroll costs reduction implemented through a tax reform in Colombia on worked hours and hourly income -- Existing studies have found mixed results, while increases in wages are commonly found, the results for employment and worked hours effects are a source of debate with no consensus on sight -- However, in line with earlier revisions of literature, we concluded that the effect of payroll costs reductions is positive and significant on both, worked hours and income -- In this paper, using socioeconomic data from Colombia we found that those individuals a effected by a payroll cost reduction between 2012-2014 exhibited significant increases in both hours and income compared to similar individuals una effected by this framework